2008
DOI: 10.1007/bf03040757
|View full text |Cite
|
Sign up to set email alerts
|

Les traumatismes de la verge: à propos de 23 cas

Abstract: RESUMELes auteurs rapportent, tl partir d'une dtude r(~trospective, 23 cas de traumatismes du p(~nis re(;us dans leur pratique quotidienne urologique au S(~n6gal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…A pool analysis of six publications (Table 1 ) from the Sub-Saharan[ 29 - 34 ] region involving 98 patients with penile trauma showed that about 75.2% of penile trauma presented fracture of the tunica albuginea with or without concomitant urethral injury. The mean age was 36.5 years with range of 0.003-73 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A pool analysis of six publications (Table 1 ) from the Sub-Saharan[ 29 - 34 ] region involving 98 patients with penile trauma showed that about 75.2% of penile trauma presented fracture of the tunica albuginea with or without concomitant urethral injury. The mean age was 36.5 years with range of 0.003-73 years.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age was 36.5 years with range of 0.003-73 years. Other penile injuries included rupture of the penile dorsal vein[ 29 ], penile contusion[ 30 ], genital mutilation, post-circumcision injury and penile gunshot injury[ 32 ]. Patients presenting with genital mutilation were either self-inflicted or due to assault.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations